Latent Iron Deficiency in Tender-Age Infants: Modern Preventive Measures - Irina A. Belyaeva; Elena P. Bombardirova; Tatyana V. Turti (Педиатрическая фармакология)
This article presents practical data, topical for pediatricians, on the child’s body provision with the essential trace element — iron; and on iron deficiency conditions development and staging in children. Clinical and laboratory criteria for the identification of such conditions are defined; data on their prevalence in tender-age infants is outlined. The results of modern studies showing the correlations between iron deficiency and delayed developmental conditions in children (including cognitive ones) are presented. Alimental factors (associated with body provision with iron) and nutritional strategies (associated with supplemental feeding timely administration, adequacy, and diversity) are described in detail. They are focused on effective and safe prevention of latent iron deficiency.